Effects of Intra- and Interspecific Plant Density on Rhizosphere Bacterial Communities - Cavalieri, Andrea; Bak, Frederik; Garcia-Lemos, Adriana M.; Weiner, Jacob; Nicolaisen, Mette Haubjerg; Nybroe, Ole (Frontiers in Microbiology, 2020)
There have been very few studies on the effects of plant competition on the rhizosphere bacterial community. To investigate the impacts of intra- and interspecific plant competition, we analyzed the responses of rhizosphere bacterial communities to plant density on the rhizosphere bacterial community as determined by 16S rRNA gene targeted sequencing. We included five weedy plant species growing in field soil in monocultures and mixed cultures at three densities in a greenhouse experiment. Our hypotheses were (1) each species gives rise to a specific bacterial rhizosphere community, the relative composition of which is not altered by plant density, (2) in a mixture of plant species, the rhizosphere bacterial community of the dominant competitor is similar to that in monoculture, while the community of a suppressed plant species will be more similar to that of the dominant species. The rhizosphere bacterial community of each species changed more with density in a mixture of all five plant species than in monocultures, so intra- and interspecific plant competition had different effects on the bacterial community. For the dominant plant competitor, Centaurea cyanus, neither intra- nor interspecific competition had major effects on the composition of the rhizosphere bacterial communities. In contrast, the bacterial communities of the weakest competitor, Trifolium repens, were affected by both intra- and interspecific competition. During increasing intraspecific competition the plant maintained a highly specialized bacterial community dominated by Rhizobium; while during interspecific competition, the relative abundance of Rhizobium declined while other nitrogen fixing and potentially plant growth promoting taxa became more abundant. Contrary to our second hypothesis, the bacterial community of the weakest competitor did not become more similar to that of the dominant species. Thus, the process of competition, as well as the plant species themselves, determined the rhizosphere bacterial community. Our results emphasize the role of plant-plant interactions for the rhizosphere bacterial community. These effects may feedback to affect plant-plant interactions, and this is an important hypothesis for future research.